Antioxidant, Membrane Stabilizing and Cytotoxic Activities of Cissus adnata (Roxb.) - Rashid, Ridwan Bin; Towsif, Farhan Nur; Bushra, Farhana Ahmed; Tahia, Faiza (Dhaka University Journal of Pharmaceutical Sciences, 2016)
The methanol extracts of whole plant of Cissus adnata (Roxb.) and their organic and aqueous soluble partitioning materials were evaluated for antioxidant, cytotoxic and membrane stabilizing properties. In the DPPH free radical scavenging assay, the aqueous extract of whole plant of C. adnata displayed the highest free radical scavenging activity with IC50 value of 4.17 ?g/ml, while the pet ether soluble fraction showed significant lethality to brine shrimps having LC50 value of 1.02 ?g/ml, as compared to the standard vincristine sulphate (LC50 value of 0.44 ?g/ml). In the evaluation for membrane stabilizing property, the pet ether soluble fraction of methanol extract of the whole plant inhibited 67.43 % and 56.60 % hypotonic solution- and heat-induced haemolysis of RBCs, respectively. Dhaka Univ. J. Pharm. Sci. 15(1): 69-71, 2016 (June)